Radiological Assessment of NORM Resulting From Oil and Gas Production Processing in South Rumaila Oil Field, Southern Iraq - Ali, Kamal K.; Shafik , Shafik Sh.; Husain , Husain A. (Iraqi Journal of Science, 2021)
Radiological assessment due to existing of natural occurring radioactive materials(NORM) in South Rumaila oil field was achieved in this study. Different samplesincluding soil, sludge, scale, oil, and water were collected from different stages ofoil and gas production in Markazia Degassing Station (SDS) in South Rumaila oilfield. Radioactivity of Ra-226, Th-232 and K-40 were measured using gammaspectrometry system based on HPGe detector with efficiency of 30%. The resultsshow that some locations within SDS are contaminated with NORM. The activity ofRa-226, Th-232 and K-40 range between 18.4 to 312.8, 9.4 to 140.8 and 66.4 to800.8 (Bq/kg) respectively. The places to be more contaminated among the otherplaces within the processing stages of oil and gas production within SDS aredehydrator and desaltor stages.